Multilateralism and regionalism from an American perspective: Parallels and contrasts with the Langhammer vision - Gary Clyde Hufbauer (Economics: The Open-Access, Open-Assessment E-Journal, 2013)
The paper discusses various milestones in the process of multilateral trade negotiations, pinpoints current challenges facing the world trading order, and proposes possible ways out of the persistent impasse. Hufbauer argues that the success of the multilateral approach is at least partly because the GATT departed from the strictly unconditional definition of the most-favored nation (MFN) rule in the late 1970s already. Regional agreements such as NAFTA complemented, rather than hindered, multilateral trade liberalization in the past. The political economy of further multilateral liberalization has become increasingly complicated since countries such as Brazil, China, and India have emerged as relevant players. Against this backdrop, Hufbauer expects regionalism to become the strongest vehicle for delivering liberalization in the future. This could still leave a bright future for the WTO as a 'house of plurilaterals', i.e., agreements on specific issues such as services liberalization with conditional MFN treatment of varying membership.
Keywords: F13; 330; GATT; WTO; regionalism; multilateralism; (un-)conditional MFN rule; Außenhandelsliberalisierung; Internationale Handelspolitik; Handelsregionalismus; WTO-Regeln; Meistbegünstigung; Welt